Visibility in health statistics: a population data linkage study more accurately identifying Aboriginal and Torres Strait Islander Births in Victoria, Australia, 1988-2008: IJPDS (2017) Issue 1, Vol 1:214 Proceedings of the IPDLN Conference (August 2016) - Ritte, Rebecca; Freemantle, Jane; Mensah, Fiona; Sullivan, Mary (International Journal of Population Data Science, 2017)
ABSTRACT Objectives An accurate picture of infant mortality informs society of its social progress. It is a key indicator of how effective public health policies and programs are in caring for the most vulnerable in our society. Currently, at the population level, Victorian data on Aboriginal and Torres Strait Islander births and deaths are excluded from Australian vital statistics. The Victorian Aboriginal Mortality Study aimed to provide a more complete and accurate population profile of Aboriginal births in Victoria using population data linkage of Victorian statutory and administrative datasets. Approach Two population statutory datasets, the Victorian Perinatal Data Collection (VPDC) and Victorian Registry of Births, Deaths and Marriages (RBDM) were linked, using probabilistic matching with mother’s name and surname, child’s date of birth and sex, for all births that occurred in Victoria between 1988 and 2008, inclusive to more accurately ascertain births to mothers and fathers who identified as Aboriginal and/or Torres Strait Islander (hereafter respectfully ‘Aboriginal’). Results Over 1.34 million files, reporting births between 1988 and 2008, were linked. However, due to data integrity issues for Indigenous identification prior to 1998, the years between 1999 and 2008 only were used in the development of the birth cohort. Matching the VPDC with the RBDM resulted in identifying an additional 4,333 live births where mother and/or father identified as Aboriginal, representing an 87% increase in the number of births previously recorded as Aboriginal by the VPDC*. The largest increase (186%) in the number of births where mother and/or father identified as Aboriginal births was observed within the Victorian metropolitan areas. Conclusion This is the first time that the VPDC and RBDM birth data were linked in Victoria. The matched birth information established a more complete population profile of Aboriginal and/or Torres Strait Islander births. These data will provide a more accurate baseline to enhance the Victorian and Australian governments’ ability to plan services, allocate resources and evaluate funded activities aimed at eliminating disparity experienced by Aboriginal and/or Torres Strait Islander peoples. Importantly, it has established a more accurate denominator from which to calculate Aboriginal infant mortality rates for Victoria, Australia. *Until 2009, the mother’s Indigenous identification only was recorded in the VPDC